Comparison of Neurocognition and Social Cognition between Schizoaffective Disorder, Mood Disorders, and Schizophrenia. - Rong Xiao; Bartel, Roxanne L.; Brekke, John (Social Work Research, 2017)
The relationship between schizoaffective disorder (SA), schizophrenia (SZ), and mood disorders (MD) is not well understood. Evaluating and comparing cognitive impairment in these disorders can help clarify how these disorders are related. The study's 47 participants with SZ, 94 with SA, and 39 with MD were evaluated with the Measurement and Treatment Research to Improve Cognition in Schizophrenia Consensus Cognitive Battery. Multivariate analysis of covariance and three Hotelling's T2 tests were used to compare cognition between participants with SZ, SA, and MD. A data mining classification tree determined the order of importance for all the significant predictors. Power analyses confirmed there was adequate statistical power. Results indicated that there was no difference between the performance of participants with SA and MD in all cognitive domains tested. Second, participants with SZ had worse performance than those with SA and MD in the cognitive domains of processing speed, working memory, visual learning, reasoning and problem solving, and social cognition, after controlling for gender, age, years of education, and substance use disorder. Finally, social cognition was the most important variable to distinguish SZ from the other two diagnoses, indicating that SA is more cognitively similar to MD than to SZ.